Pengaruh Leverage Terhadap Manajemen Laba - Astari Dianty (LPPM UNIBI, 2021)
The main objective of this study is to obtain empirical evidence on the effect of leverage on earnings management in manufacturing companies in the basic industrial sector and chemicals listed on the Indonesian stock exchange. The data population was 63 manufacturing companies in the period 2015 - 2019. The sample was taken by purposive sampling, where only 6. The data analysis used in this study is testing classical assumptions and linier regression analysis. Research partially proves that leverage hasn’t an effect on earnings management.